PENGARUH KOMPETENSI AUDITOR DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT PADA KAP DI KOTA MEDAN - Syahputra, Oky; Aristantya, Selvi; hawari, Rifqi (Fakultas Ekonomi Prodi Akuntansi, 2025)
This study aims to analyze the effect of auditor competence and independence on audit quality at public accounting firms in Medan. Competence and independence are two important factors that influence the quality of audits produced by auditors. The research method used was a quantitative approach with a sample of 32 auditors obtained from 7 public accounting firms in Medan. Data testing was conducted using validity tests, reliability tests, classical assumption tests, and multiple linear regression. The results of the test show that the data analysis using partial tests (t-test) shows that: (1) Auditor competence does not have a significant effect on audit quality. (2) Auditor independence does not have a significant effect on audit quality. The results of data testing using the (F-test) indicate that: (3) Auditor competence and independence do not have a significant effect simultaneously on audit quality.